Introduction to Cloud Security with Microsoft Azure - Lowe, Riaan (Packt Publishing, 2020)
Get up to speed with effectively securing your cloud systems About This Video Understand the key differences between different hosting environments Learn the basics of cloud computing and cloud architecture Find out how to secure cloud systems with the help of Microsoft Azure In Detail Every organization is now migrating to the cloud to save money, but is it really safe? If you're looking to learn about the cloud and how to effectively secure it, as well as build your own virtualized networks inside the Microsoft Azure cloud computing platform, then you're in the right place! In this course, you will learn the fundamentals of cloud-based service technologies, as well as how to secure them. All along, you'll not only learn the theory but also get hands-on experience. You'll understand how to set up your own cloud architecture and protect your cloud systems. As you progress, this course will give you the opportunity to apply your knowledge in the real world by creating your own virtualized network inside the Microsoft Azure cloud computing platform. To build on your knowledge further, you'll get to grips with the difference between on-premise and hosted solutions, as well as SaaS, PaaS, and IaaS. Later, you'll cover single-tenancy and multi-tenancy solutions, along with their security concerns. By the end of this course, you will have gained the skills you need to confidently secure your cloud systems with Microsoft Azure.